Post-operative complications following cervical ventral slot in dogs: a retrospective review of the influence of prophylactic fenestration and chondrodystrophy in 593 cases - Dupont, Christophe Osterreicher Cunha; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2025)
IntroductionCervical intervertebral disc herniation is a significant health concern in dogs, leading to pain, neurological deficits, and a high rate of recurrence that can compromise both quality of life and long-term mobility. Prophylactic fenestration has demonstrated benefits in reducing recurrence in the thoracolumbar spine. Although its application in the cervical spine remains debated, it is routinely performed in some practices with the aim of preventing future disc herniations. However, no published data have previously addressed the safety or perioperative risks of cervical prophylactic fenestration.ObjectiveTo describe the frequency, distribution, and clinical associations of prophylactic fenestration performed during cervical decompressive surgery, and to assess its relationship with perioperative complications.Materials and methodsA retrospective review of clinical records from a single referral institution (2010–2020) was conducted of dogs undergoing cervical ventral slot surgery for intervertebral disc extrusion. Associations between prophylactic fenestration, complications, and clinical variables were evaluated statistically.ResultsOf 593 dogs undergoing cervical ventral slot surgery, 66.8% (396/593) received one or more prophylactic fenestrations. Fenestration was significantly more common in chondrodystrophic (CD) breeds (72.9%) compared to non-chondrodystrophic breeds (51.7%) (p < 0.001). The overall post-operative complication rate was 10.6% (63/593), with no significant association between complications and fenestration (p = 0.763), chondrodystrophy (p = 0.306) or site of herniation (p = 0.142).ConclusionProphylactic fenestration performed during cervical ventral slot surgery was not associated with an increased risk of perioperative complications. The significantly higher use of fenestration in chondrodystrophic dogs likely reflects their predisposition to early disc degeneration. These findings support the perioperative safety and potential effectiveness of fenestrations, particularly in dogs predisposed to disc degeneration. Prospective studies are warranted to evaluate its long-term benefits and biomechanical implications.